IMPLEMENTASI KEBIJAKAN PENDIDIKAN, POLA INTERAKSI SANTRI, DAN EFEKTIVITAS PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI PONDOK PESANTREN ASSUJA'I ROWOTAMTU RAMBIPUJI JEMBER - Maksum; Titin Nurhidayati; Sugiyanto (PT. Hasba Edukasi Mandiri, 2026)
This study aims to describe and analyze the implementation of educational policies, student interaction patterns, and the effectiveness of Islamic Religious Education (PAI) learning at Pondok Pesantren Assuja'i Rowotamtu, Rambipuji, Jember. Using a qualitative case study approach with Edwards III's policy implementation theory, this research examines four implementation variables—communication, resources, disposition, and bureaucratic structure—as well as their relationship to the formation of student social interactions and the effectiveness of PAI learning. Data were collected through in-depth interviews, participatory observation, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña. This research produces a conceptual recommendation of the MPIS-BAP Model (Pesantren Rule-Based Student Interaction Management Model) as an integrative synthesis that connects policy, supervision, student interaction, and learning effectiveness. The contribution of this research enriches the discourse on Islamic educational policy management while providing practical guidance for pesantren administrators in creating a conducive learning environment grounded in Islamic values.